Pengembangan Modul Fisika Materi Suhu dan Kalor Terintegrasi Ayat Al-Qur’an - Ratih Widya Ningsi; Hasbullah Hasbullah; Muhammad Qaddafi (Pendidikan Fisika UIN Alauddin Makassar, 2025)
This study addresses the challenge of engaging students in traditional physics education, particularly in Islamic contexts where integrating spirituality is often difficult. It presents a developed physics module for Grade XI students at MAN 1 Selayar that combines Quranic verses with temperature and heat concepts, using the 4D development model (Define-Design-Develop). The module bridges scientific understanding with Islamic values, and its effectiveness was tested with 20 students. Expert validation resulted in a high 0.94 validity score, confirming its scientific accuracy. Student feedback was overwhelmingly positive, with 90% rating the module as